El pat a una mano vs el pat a dos manos en golf. Test de campo - Martorell Aroca, Juan; Barriopedro Moro, Maribel (KRONOS, 2007)
Putt means 45% of all hits for a profesional golf player. Any improvement in performance with that stick would get a better game for the player. All techniques used for that hit are made with both hands, however, when a nos strong and precise one is needed just one hand is used. Why not the same? This article goal is to demonstrate that one hand putt is a great alternative for many players.Results using two different techniques have been compared: most famous two hands putt and one hand putt. First experience with 53 golf starters and deserving to learn. After observing no significant improvement with either technique we decided to test 21 pro or Spain National Teams players, 14 male and 7 female. This group results were better with only one hand than starters, although no significant differences in any case. It is specially noticeable that out of those 21, 10 (47,6%) had a lower score with just one hand than with both, opposite to 7 (33,3%) hitting better with both, and 4 (19,1%) doing the same with either technique.This test confirms better accuracy with just one hand putt in either distance, even though players are not familiar with that techinique, better for certain players, then, thar the rest of the styes used in this game situation.